Chirality Synchronization of Hydrogen‐Bonded Complexes of Achiral N‐Heterocycles. (29th November 2016) - Buchs, Jens; Vogel, Laura; Janietz, Dietmar; Prehm, Marko; Tschierske, Carsten
Abstract: 2, 4‐Diamino‐6‐phenyl‐1, 3, 5‐triazines carrying a single oligo(ethylene oxide) (EO) chain form an optically isotropic mesophase composed of a conglomerate of macroscopic chiral domains with opposite sense of chirality even though the constituent molecules are achiral. This mesophase was proposed to result from the helical packing of hydrogen‐bonded triazine aggregates, providing long‐range chirality synchronization. The results provide first evidence for macroscopic achiral symmetry breaking upon conglomerate formation in an amorphous isotropic phase formed by hydrogen‐bonded associates of simple N‐heterocycles that are related to prebiotic molecules. Abstract : Spontaner Symmetriebruch gelang mit einfachen achiralen wasserstoffverbrückten Heterocyclen, die präbiotischen Molekülen ähneln, durch die Bildung von Konglomeraten aus chiralen Domänen mit entgegengesetzter Händigkeit. Diese optisch isotropen Mesophasen resultieren wahrscheinlich aus der helikalen Anordnung der wasserstoffverbrückten Triazin‐Aggregate.